Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil - Ohara, Willian M.; Lima, Flávio C. T.; Barros, Bruno S. (Zootaxa, 2017)
A new species of Hyphessobrycon is described from the rio Roosevelt, rio Madeira basin, Mato Grosso State, Brazil. Hyphessobrycon petricolus sp. n. can be distinguished from its congeners by the unique combination of the following features: a well-defined, relatively narrow dark midlateral stripe on body extending from immediately behind posterior margin of opercle to the middle caudal-fin rays, relatively conspicuous humeral blotch, and 16–20 branched anal-fin rays. Comments on the remaining Hyphessobrycon species presenting a conspicuous dark midlateral stripe are presented.